Diskretni plinski kavitacijski model z upoštevanjem vpliva nestalnega kapljevinskega trenja v cevi - Bergant, Anton (Strojniški vestnik, 2005)
Transient, vaporous, cavitating pipe flow occurs when the pressure drops to the liquidćs vapour pressure. A brief description of the method of the characteristics and fundamentals of unsteady pipe-flow friction and transient,cavitating pipe flow are given. The main objective of this paper is to present a novel, discrete gas-cavity model (DGCM) with a consideration of unsteady frictional effects. The numerical results are compared with the results from laboratory measurements. The inclusion of unsteady friction into the DGCM significantly improves the numerical results.
Keywords: sistemi cevni; udari vodni; tok kavitacijski; kavitacija; hidrodinamika; trenje